2004
DOI: 10.1016/j.chembiol.2004.08.017
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid Nonribosomal Peptide-Polyketide Interfaces in Epothilone Biosynthesis

Abstract: Epothilone (Epo) D, an antitumor agent currently in clinical trials, is a hybrid natural product produced by the combined action of nonribosomal peptide synthetases (NRPS) and polyketide synthases (PKS). In the epothilone biosynthetic pathway, EpoB, a 165 kDa NRPS is inserted into an otherwise entirely PKS assembly line, forming two hybrid NRPS-PKS interfaces. In light of the terminal linker effect previously identified in PKS, the N- and C-terminal sequences of EpoB were examined for their roles in propagatin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
30
0
2

Year Published

2005
2005
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 43 publications
0
30
0
2
Order By: Relevance
“…In the three-protein synthase that produces the aglycone scaffold of erythromycin, 6-deoxyethronolide B, Khosla and coworkers (10) have demonstrated that appending these short linker regions onto noncognate donor carrier proteins allows for recognition by downstream elongation modules. In the hybrid PKS͞NRPS interface of the first two modules of epothilone biosynthesis, our laboratory has shown that removal of these linker regions disrupts the channeling of thiotemplated substrate intermediates to the downstream module (11,36). In addition, similar communication-mediating domains have been discovered in the NRPS that produces tyrocidine (12).…”
Section: Discussionmentioning
confidence: 87%
“…In the three-protein synthase that produces the aglycone scaffold of erythromycin, 6-deoxyethronolide B, Khosla and coworkers (10) have demonstrated that appending these short linker regions onto noncognate donor carrier proteins allows for recognition by downstream elongation modules. In the hybrid PKS͞NRPS interface of the first two modules of epothilone biosynthesis, our laboratory has shown that removal of these linker regions disrupts the channeling of thiotemplated substrate intermediates to the downstream module (11,36). In addition, similar communication-mediating domains have been discovered in the NRPS that produces tyrocidine (12).…”
Section: Discussionmentioning
confidence: 87%
“…The N-terminal 55 residues of the EpoB protein make up the docking domain (EpoBdd), which recognizes the upstream EpoAdd to position the acetyl-S-EpoA-T domain for catalysis (24). EpoBdd adopts an αββαα fold, consisting of an initial α-helix, β-turn, and two final α-helices ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The boundary between the 57 kDa amino-terminal Cy domain and the subsequent internal A domain was assigned to a loop identified by secondary structure prediction, as undertaken for the EntF C domain (8). Since the initial 56 amino acids of the N-terminus of EpoB have previously been shown to be required for communication with the upstream subunit EpoA(ACP), this amino-terminal region was retained in its entirety (20). Two possible sites for the EpoB(Cy) C-terminus were designated Glu492 and Gln497.…”
Section: Construction and Purification Of Epob(cy)mentioning
confidence: 99%